Building on Self-efficacy for Experienced Family Caregivers: The Savvy Advanced Program. (12th March 2018) - Samia, Linda W; O'Sullivan, Ann; Fallon, Kate Cole; Aboueissa, AbouEl-Makarim; Hepburn, Kenneth W
Abstract: Background and Objectives: The Savvy Advanced psychoeducation program was designed for previously trained caregivers of persons living with dementia to refine their problem-solving and planning skills and enhance their sense of self-efficacy as dementia progressed for the care recipient. Implementation, feasibility, participant satisfaction, and perceived program benefits were also evaluated. Research Design and Methods: A total of 100 dementia family caregivers participated in the 12-month evaluation of Savvy Advanced. A pragmatic quasi-experimental no control design was used to examine changes in caregiver self-efficacy, competence, personal gain, skill mastery, and symptoms of depression from baseline to 5 and 12 months postintervention. Implementation feasibility, and participant satisfaction and perceived program benefits, were also evaluated. Results: Having previously participated in a psychoeducation intervention, caregivers were quickly engaged and interactive. Caregivers demonstrated significant improvement in competence, personal gain, self-efficacy, and symptoms of depression at 5 months postprogram. Gains were sustained for competence and personal gain at 12 months. Caregivers were highly satisfied with the program and supporting materials. Challenges to implementation included caregiver recruitment and trainer sustainability. Discussion and Implications: Caregivers can benefit from episodic interventions as their situation changes and new challenges arise. Savvy Advanced is one means to address these needs. Evaluation in a randomized trial is required to establish efficacy; examination of alternative modes of delivery for caregivers unable to attend in person is warranted.